If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 20 = 34 Reorder the terms: 20 + 6x = 34 Solving 20 + 6x = 34 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-20' to each side of the equation. 20 + -20 + 6x = 34 + -20 Combine like terms: 20 + -20 = 0 0 + 6x = 34 + -20 6x = 34 + -20 Combine like terms: 34 + -20 = 14 6x = 14 Divide each side by '6'. x = 2.333333333 Simplifying x = 2.333333333
| -2y-7=-13 | | 7b+12=31b | | 4(-0.4+-0.29)-3y=-13 | | 8x+22=-28 | | -6x+(7x+2)-(x-9)=19 | | |3x-8|-|3x-2|=6 | | 44-3x=8-9x | | 9x+1=8x+2 | | 11+(2-9x)=15-(2x+9) | | -11=6b+5b | | 5x-20=x+3 | | y^3=8-x | | 5z-2(z-8)=3(y-3z)+12 | | -9c-(-7c+1)=16 | | 24n=15n-81 | | 5+7+2+6+y+(y+1)+7+4=5 | | (x+7)(7x-1)=x+3 | | (3x-11)+(2x+7)= | | -3a-(a+2)-(a-4)=5a | | -4x+33= | | (3x-5)(x+14)=0 | | 7+30x=20x+15 | | 5+4X=-8 | | X=2.4+0.4(-71) | | 3t-5=5t-3 | | 0.6(6-0.3n)=-2.1 | | 0.54=0.36m | | -3(x+1)-5(x+1)-6(x-1)=10 | | 42+5x=-2x | | 3x+4+5x+1+2x+5=2x+x+13 | | 10(5)-13(5)= | | =x-x |